The use of electronic modules based on socio-scientific issues to improve argumentation skills and Students' perceptions of biotechnology - Fitri Husni Mardiyah; Widi Purwianingsih; Rini Solihat (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
Argumentation abilities can be developed using electronic modules based on socio-scientific issue themes in biotechnology materials. The purpose of this project is to gather data regarding the efficacy of using electronic modules centered on socio-scientific issues to enhance students' perceptions of biotechnology and their ability to argue. A quasi-experimental approach was taken in this investigation. The non-equivalent control group design is the research methodology employed. The sample consisted of 120 students from Class XII who were selected with the purposive sampling technique. The experimental group was taught using a socio-scientific issue-based electronic module integrated with a problem-based learning model, whole the control group received instruction using a conventional electronic module without socio-scientific issue integration. The findings demonstrated that there was a significant average difference in argumentation skills between the experimental and control classes. The results of the Mann-Whitney test on the value of argumentation skills indicate that there is a difference in the effectiveness of utilizing regular modules to increase students' argumentation abilities against electronic modules based on socio-scientific issue issues is 0.002 (2-tailed = 0.002) < (0.05). The findings indicated that the average difference between the experimental class and the control class was significant in students' perceptions of biotechnology. The findings demonstrated that students' perceptions of biotechnology differed significantly on average across the experimental and control classes. According to the results of the Mann-Whitney test on the value of students' perceptions of biotechnology, the effectiveness of using electronic modules based on socio-scientific issue issues differs from that of regular modules in terms of improving students' perceptions of biotechnology is 0.003 (2-tailed = 0.003) < (0.05). The N-Gain score requirements for enhancing students' reasoning skills through the use of electronic modules centered on socio-scientific issue topics.